Magnetic poly(glycidyl methacrylate) microspheres for protein capture - Koubková, Jana; Müller, Petr; Hlídková, Helena; Plichta, Zdeněk; Proks, Vladimír; Vojtěšek, Bořivoj; Horák, Daniel (New biotechnology, 2014)
The efficient isolation and concentration of protein antigens from complex biological samples is a critical step in several analytical methods, such as mass spectrometry, flow cytometry and immunochemistry. These techniques take advantage of magnetic microspheres as immunosorbents. The focus of this study was on the development of new superparamagnetic polymer microspheres for the specific isolation of the tumor suppressor protein p53. Monodisperse macroporous poly(glycidyl methacrylate) (PGMA) microspheres measuring approximately 5 μm and containing carboxyl groups were prepared by multistep swelling polymerization of glycidyl methacrylate (GMA), 2-[(methoxycarbonyl)methoxy]ethyl methacrylate (MCMEMA) and ethylene dimethylacrylate (EDMA) as a crosslinker in the presence of cyclohexyl acetate as a porogen. To render the microspheres magnetic, iron oxide was precipitated within their pores; the Fe content in the particles received ∼18 wt%. Nonspecific interactions between the magnetic particles and biological media were minimized by coating the microspheres with poly(ethylene glycol) (PEG) terminated by carboxyl groups. The carboxyl groups of the magnetic PGMA microspheres were conjugated with primary amino groups of mouse monoclonal DO-1 antibody using conventional carbodiimide chemistry. The efficiency of protein p53 capture and the degree of nonspecific adsorption on neat and PEG-coated magnetic microspheres were determined by western blot analysis.
Keywords: Polymethacrylic Acids; myši; Animals; myší monoklonální protilátky; Cell Line, Tumor; Tumor Suppressor Protein p53; Polyethylene Glycols; Antibodies, Monoclonal, Murine-Derived; zvířata; polyethylenglykoly; Mice; Microspheres; nádorový supresorový protein p53; kyseliny polymethakrylové; mikrosféry; nádorové buněčné linie